2017
DOI: 10.1038/s41467-017-00510-x
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation at enhancers identifies distinct breast cancer lineages

Abstract: Breast cancers exhibit genome-wide aberrant DNA methylation patterns. To investigate how these affect the transcriptome and which changes are linked to transformation or progression, we apply genome-wide expression–methylation quantitative trait loci (emQTL) analysis between DNA methylation and gene expression. On a whole genome scale, in cis and in trans, DNA methylation and gene expression have remarkably and reproducibly conserved patterns of association in three breast cancer cohorts (n = 104, n = 253 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
129
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(142 citation statements)
references
References 59 publications
13
129
0
Order By: Relevance
“…However, little attention has been given to DNA methylation at other non-coding regions. We recently showed that DNA methylation at enhancers identifies distinct breast cancer lineages [2]. The epigenome and the chromatin landscape are important features to explain breast cancer development and also progression, as recently demonstrated for endocrine resistance in breast cancer [4].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, little attention has been given to DNA methylation at other non-coding regions. We recently showed that DNA methylation at enhancers identifies distinct breast cancer lineages [2]. The epigenome and the chromatin landscape are important features to explain breast cancer development and also progression, as recently demonstrated for endocrine resistance in breast cancer [4].…”
Section: Introductionmentioning
confidence: 79%
“…ATAC-seq data from TCGA confirmed that the regions surrounding these CpGs were more accessible (open) in ER positive than in ER negative tumors (Wilcoxon p-value = 6.38e-5; Figure 2b). Furthermore, using the UniBind [28] database storing direct TF-DNA interactions for 231 TFs using 1983 human ChIP-seq data sets, we found cluster 1 CpGs enriched at FOXA1/2, GATA2/3, TFAP2C, and ESR1 (encoding ER-alpha) binding sites; these TFs are known to drive ER positive breast cancers [2,30] (Figure 2c). Unsupervised clustering of the DNA methylation values Enhancer=Biv_Enh, Active Intergenic Enhancer=Act_Intergen_Enh.…”
Section: Cluster 1 Cpgsmentioning
confidence: 98%
See 1 more Smart Citation
“…Of the co-regulatory factors, cohesin could be used as a mark of an enhancer [65,4]. DNA methylation data has also been used to predict enhancers [66]. Other potential useful features could be the information about the CpG islands, phastCons evolutionary conservation scores, TF motifs or DNA sequence itself.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using RNA-seq and ChIP-seq analysis of the acetylation of lysine 91 27 on histone 3 (H3K27ac), an established active enhancer marker, revealed that epigenetic 92 activation of the cholesterol biosynthesis pathway causes activation of ERα resulting in 93 resistance (10). DNA methylation has also been shown to be perturbed during breast cancer 94 development and may largely affect gene expression (4,11) Since DNA methylation has also 95 been shown to be altered in endocrine resistant tumours (12) the identification of methylation 96 markers for disease diagnosis, prognosis, and treatment outcome is receiving increased 97 attention. Moreover, breast cancer treatment might benefit from the regulation of methylation 98 activity by using DNA methyltransferase inhibitors (4).…”
Section: Introduction 69mentioning
confidence: 99%